Kontribusi Pendapatan Nelayan Ikan Hias Terhadap Pendapatan Total Rumah Tangga di Desa Serangan - SIHOMBING, FEBRY; ARTINI, NI WAYAN; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.2, No.4, Oktober 2013, 2013)
ABSTRACT Contribution Revenue Ornamental Fish Fishermen Against Total Household Income in the SeranganVillage The purpose of this study was to determine : ( 1) the costand revenue  structure fishermen fish in the Serangan Village ( 2) ornamental fish revenue contribution to total household income of fishermen fish in the Serangan Village ( 3) The constraints faced by fishermen ornamental fish culture in running the business . The method used in this study consisted of observation , in-depth interviews , literature review and survey . Data have been obtained were then analyzed by the method of farm analysis . Research results indicate that ( 1) The average cost of production of ornamental fish business in the village of attack is Rp10.247.084,00/cycle consisting of variable cash cost of   Rp 6.405.430.00 ( 62,51%), variable costs instead of cash amounting to Rp 2.447.059,00 ( 23,88%), and a flat fee of Rp 1.394.595,00 ( 13,61%) and the average amount of revenue obtained from the fishermen ornamental fish farming in the amount of   Rp . 17.329.412.00/cycle and The average income of the fishermen of ornamental fish farming in the Serangan Village is Rp . 7.082.328.00/cycle ( 2) Contribution to the cultivation of ornamental fish total household income of fishermen in the village was 48,56 % Attack This means income from ornamental fish farming contributes greatly to the total household income of fishermen . ( 3) The constraints or problems faced by fishermen in the cultivation of ornamental fish disease during weather disturbances which makes fishing difficult to regulate the temperature of the water in the pond/aquarium that can bedetrimental to fishermen . Keywords : fisherman , cost structure, analysis farming .